The Antifungal Activity of Loquat (Eriobotrya japonica Lindl.) Leaves Extract Against Penicillium digitatum - Shen, Yuting; Chen, Chuying; Cai, Nan; Yang, Ruopeng; Chen, Jinyin; Kahramanoǧlu, İbrahim; Okatan, Volkan; Rengasamy, Kannan R. R.; Wan, Chunpeng (Frontiers in Nutrition, 2021)
This study reveals the antifungal activity of loquat leaves extracts (LLE) against the citrus postharvest pathogen Penicillium digitatum (P. digitatum). The LLE exhibited intense antifungal activity against P. digitatum, with a minimum inhibitory concentration (MIC) of 0.625 mg/mL and a minimum fungicidal concentration (MFC) of 1.25 mg/mL, respectively. The significant inhibitory effects of LLE on mycelial growth and spore germination of P. digitatum were seen in a dose-dependent manner. Simultaneously, to investigate the possible antifungal mechanisms by LLE, we analyzed their influence on morphological changes by scanning electron microscopy (SEM) and cell membrane permeability, integrity of cell wall and cell membrane, and adenosine triphosphate (ATP) levels. Alterations such as sunken surface and malformation were occurred in the LLE-treated P. digitatum spores by SEM observation. Furthermore, the intracellular inclusions contents decreased after LLE treatment, indicating the increase of cell membrane permeability. An increase in membrane permeability improves LLE penetration into the cell and speeds up cell death due to the damage to the plasma membrane. Besides, LLE treatment induced a significant decline of the intracellular energy substances (ATP, ADP, and AMP) content with a noticeable addition of the extracellular ATP, ADP, and AMP during the entire treatment period. Those results manifest that the antifungal activity of LLE against P. digitatum can be attributed to the derangement of cell membrane permeability and the disordered energy metabolism.